Avaliação do rendimento e custo operacional do forwarder na colheita de eucalipto em primeiro e segundo corte - Coneglian, Ademilson; Batista, Wagner Roberto [UNESP]; Hokama, Luciana Ferreira [UNESP]; Santiago, Francisco Luiz Sanchez [UNESP]; Fenner, Paulo Torres [UNESP] (My University, 2010)
This project aimed to evaluate the forwarder operating income within two timber harvest subsystems in Eucalyptus forests. The technical analysis included studies of time, movements and productiveness. The economic analysis included operating costs and extraction costs parameters. The load and unload time, together, match more than 2/3 of the total operating cycle of the forwarder, in both subsystems. The periods of time of unloaded trip and loaded trip were directly influenced by the extraction average distance to be gone through. The extraction costs were lower in the first harvest compared to the second harvest.

Propôs-se, como objetivo primeiro deste trabalho avaliar o rendimento operacional do forwarder em dois subsistemas de colheita florestal de madeira curta, de florestas de Eucalyptus. A avaliação técnica dos rendimentos operacionais e dos custos de extração, baseou-se em um estudo de tempos e movimentos. Os tempos de carregamento e descarregamento, corresponderam juntos, a mais de 2/3 do tempo total do ciclo operacional do forwarder, em ambos os subsistemas. O tempo de viagem vazia e viagem carregada foram influenciados diretamente pela distância de extração. O custo de extração de madeira foi menor no subsistema de primeiro corte em comparação ao segundo corte.
Assessment of the performance and operational cost of the forwarder to harvest eucalyptus in first and second cut
Keywords: Timber harvesting; Logging cost and forest mechanization; Colheita florestal; Extração de madeira; Baldeio e mecanização florestal